TIA concrete mix design nomograph - 293419 Lee, Yee Loon; Mohd. Warid Hussin, 1950-; Khoo, K. O.; Asia-Pacific Structural Engineering & Construction (APSEC 2000) (4th : 2000 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2000)
09